Intraosseous foreign-body granuloma in the mandible subsequent to a 20-year-old work-related accident - Sarmento Silveira, Vanessa Avila; do Carmo, Elaine Dias; Dias Colombo, Carlos Eduardo [UNESP]; Rodrigues Cavalcante, Ana Sueli [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (Medicina Oral S L, 2008)
The purpose of this article was to describe the clinical and microscopic features of an intraosseous foreign-body granuloma in the mandible that developed after the traumatic implantation of metal fragments during a work-related accident. A 65-year-old male patient had a severe pain in the body of mandible. Clinical examination showed facial asymmetry and a scar, extending to the left mental region. Intraoral examination revealed a soft mass involving the left alveolar bone with normal appearance of the mucosa surface. Panoramic radiographs showed a radiolucent lesion along the mandible extending from the central incisive to the first molar. Computed tomography revealed an osteolytic mass in the same area. His medical history included a work-related accident twenty years prior to evaluation. During the biopsy an important amount of bright metal-like pieces surrounded by soft tissue were found. A microscopic examination showed a foreign body associated with an aggregation of multinucleated giant cells. The final diagnosis was a foreign body granuloma. Even though foreign-body granulomas in the mandible are rare lesions, dentists should be familiar with their features and include them in the differential diagnosis of tissue masses.
Keywords: Granuloma; foreign-body; mandible; giant cells; inflammation